PENGARUH PENAMBAHAN LENO-WEAVE FIBER TERHADAP KEKUATAN TEKAN RESTORASI RESIN COMPOSITE - Wahyuni, Sri; Adriyoso, Helios; smalayani, smalayani (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2013)
Composite is one of filling materials of dentistry which is qualified enough and often used in mature or children. Composite is used because of its good aesthetics but its strenght for posterior tooth is less. In wide or large posterior tooth caries, it needs filling material which has very big strenght because it will be used to chew food. Therefore, it should use amalgam filling material which has been proven having bigger strenght than restoration which has the same color with tooth. Amalgamrestoration has high toxic metallic mercury content so that the writter was willing to find alternative method in using restoration material which has the same color with tooth but it has high pressure power. Fiber used mostly often in dentistry is leno-wave fiber used in laboratory products and in clinical application. The aim of this research was to know whether there is an effect of leno-weave fiber adding towards pressure power of resinous composite restoration. It was experimental research. The place of research was in mechanical laboratory of State Polytechnic of Sriwijaya Palembang. The whole amount of samples was 25 and divided into 5 groups. This research result showed that there was an effect of leno-weave fiber adding towards the increase of pressure power of resinous composite restoration. The highest increase was on leno-weave fiber adding of diameter 4 mm andcross position whose pressure power was 269.074 N/mm2. The cause was that leno-weave fiber was able to enhance physical character of resin composite restoration and with plaiting form it was able to continue chewing pressure in order to be resistant to pressure.